2016
DOI: 10.18559/soep.2016.10.7
|View full text |Cite
|
Sign up to set email alerts
|

ISO 14001 certification: benefits, costs and expectations for organization

Abstract: Abstract:In the globalized market, the certification of Environmental Management Systems (EMS), according to ISO 14001 standard, introduced about 20 years ago and reviewed in 2015, is becoming increasingly strategic.In the last decade, the implementation of the EMSs was widely "metabolized" by organizations, because in this certification scheme, the decision maker recognizes, in the face of significant economic and organizational efforts, the opportunity to enjoy significant benefits from a variety of critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
0
8
0
3
Order By: Relevance
“…Some opinions consider that EMS integration increase the costs of the companies and do not determine a high performance [67]. Others consider that EMS integration determines real benefits at the organizational level, at the level of environmental performance, efficiency, and profitability [84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some opinions consider that EMS integration increase the costs of the companies and do not determine a high performance [67]. Others consider that EMS integration determines real benefits at the organizational level, at the level of environmental performance, efficiency, and profitability [84].…”
Section: Discussionmentioning
confidence: 99%
“…Link and Naveh [61] noted that "in practice, however, studies have been unable to definitively show that ISO 14001 either leads or does not lead to improvements in environmental and business performance" [75,[80][81][82][83]. However, Pesce and his collaborators [29] citing the literature mentioned that "studies point out that ISO 14001 brings three types of benefits: environmental performance, efficiency and profitability" [84].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Sambasivan and Fei () analysed critical success factors for implementing ISO 14001 in Malaysia; they concluded that a general lack of environmental skills could affect the success of an implementation. These skills can be linked to activities such as identifying environmental impacts and aspects, auditing, and measuring environmental performance (Di Noia & Nicoletti, ; Nawrocka, Brorson, & Lindhqvist, ; Ozusaglam, Robin, & Wong, ; Russo, ). On this note, Boiral () argued that to achieve ISO 14001 certification, many companies must take on specialised environmental consultants and technicians.…”
Section: Factors That Affect the Success Of An Iso 14001 Implementationmentioning
confidence: 99%
“…Studies indicate that the adoption of ISO 14001 does not always translate into environmental and financial benefits, and that a series of drawbacks that hinder potential gains can also be identified [10,[57][58][59][60]. Studies point out that ISO 14001 brings three types of benefits: environmental performance, efficiency and profitability [61]. However, Whitelaw [62] indicates that the main benefits are generally identified by firms as: gain of a "green image" resulting in gains in market shares; ability to attract new investors; reduction of insurance and prosecution risks; and reduction of costs.…”
Section: Environmental Management Systems (Ems)mentioning
confidence: 99%